Iron in neuronal function and dysfunction - Salvador, Gabriela Alejandra (2010)
Iron (Fe) is an essential element for many metabolic processes, serving as a cofactor for heme and nonheme proteins. Cellular iron deficiency arrests cell growth and leads to cell death; however, like most transition metals, an excess of intracellular iron is toxic. The ability of Fe to accept and donate electrons can lead to the formation of reactive nitrogen and oxygen species, and oxidative damage to tissue components; contributing to disease and, perhaps, aging itself. It has also been suggested that iron-induced oxidative stress can play a key role in the pathogenesis of several neurodegenerative diseases. Iron progressively accumulates in the brain both during normal aging and neurodegenerative processes. However, iron accumulation occurs without the concomitant increase in tissue ferritin, which could increase the risk of oxidative stress. Moreover, high iron concentrations in the brain have been consistently observed in Alzheimer´s disease (AD) and Parkinson´s disease (PD). In this regard, metalloneurobiology has become extremely important in understanding the role of iron in the onset and progression of neurodegenerative diseases. Neurons have developed several protective mechanisms against oxidative stress, among them the activation of cellular signaling pathways. The final response will depend on the identity, intensity, and persistence of the oxidative insult. The characterization of the mechanisms involved in high iron induced in neuronal dysfunction and death is central to understanding the pathology of a number of neurodegenerative disorders.